Aquaporins in Acute Brain Injury: Insights from Clinical and Experimental Studies - Stelios Kokkoris; Charikleia S. Vrettou; Nikolaos S. Lotsios; Vasileios Issaris; Chrysi Keskinidou; Kostas A. Papavassiliou; Athanasios G. Papavassiliou; Anastasia Kotanidou; Ioanna Dimopoulou; Alice G. Vassiliou (Biomedicines)
Aquaporins (AQPs) are a family of transmembrane water channel proteins facilitating the transport of water and, in some cases, small solutes such as glycerol, lactate, and urea. In the central nervous system (CNS), several aquaporins play crucial roles in maintaining water homeostasis, modulating cerebrospinal fluid (CSF) circulation, regulating energy metabolism, and facilitating neuroprotection under pathological conditions. Among them, AQP2, AQP4, AQP9, and AQP11 have been implicated in traumatic and non-traumatic brain injuries. The most abundant aquaporin (AQP) in the brain, AQP4, is essential for fluid regulation, facilitating water transport across the blood–brain barrier and glymphatic clearance. AQP2 is primarily known for its function in the kidneys, but it is also expressed in brain regions related to vasopressin signaling and CSF dynamics. AQP9 acts as a channel for glycerol and lactate, thus playing a role in metabolic adaptation during brain injury. AQP11, an intracellular aquaporin, is involved in oxidative stress responses and cellular homeostasis, with emerging evidence suggesting its role in neuroprotection. Aquaporins play a dual role in brain injury; while they help maintain homeostasis, their dysregulation can exacerbate cerebral edema, metabolic dysfunction, and inflammation. In traumatic brain injury (TBI), aquaporins regulate the formation and resolution of cerebral edema. In non-traumatic brain injuries, including ischemic stroke, aneurysmal subarachnoid hemorrhage (aSAH), and intracerebral hemorrhage (ICH), aquaporins influence fluid balance, energy metabolism, and oxidative stress responses. Understanding the specific roles of AQP2, AQP4, AQP9, and AQP11 in these brain injuries may lead to new therapeutic strategies to mitigate secondary damage and improve neurological outcomes. This review explores the function of the above aquaporins in both traumatic and non-traumatic brain injuries, highlighting their potential and limitations as therapeutic targets for neuroprotection and recovery.